2014
DOI: 10.1186/1465-9921-15-34
|View full text |Cite
|
Sign up to set email alerts
|

JNK suppresses pulmonary fibroblast elastogenesis during alveolar development

Abstract: BackgroundThe formation of discrete elastin bands at the tips of secondary alveolar septa is important for normal alveolar development, but the mechanisms regulating the lung elastogenic program are incompletely understood. JNK suppress elastin synthesis in the aorta and is important in a host of developmental processes. We sought to determine whether JNK suppresses pulmonary fibroblast elastogenesis during lung development.MethodsAlveolar size, elastin content, and mRNA of elastin-associated genes were quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
(43 reference statements)
1
12
0
Order By: Relevance
“…The data from SPC-TNF-a mice in this study are in line with a study showing that mice lacking JNK1 are protected against TGF-b-induced pulmonary fibrosis and fibrotic gene expression (31,32). This is also supported by another study showing that JNK knockout mice were found to have an increased pulmonary elastin content compared with wild-type mice, and showed increased elastogenesis, but had impaired alveolar septation during lung development (33). In addition, the JNK inhibitor, SP600125, partly prevented bleomycin-induced hydroxyproline and a smooth muscle actin levels in the lung tissue of rats, and thalidomide, an immunomodulatory drug able to suppress the generation of TNF-a, prevented the induction of JNK phosphorylation and hydroxyproline and a smooth muscle actin levels even more (34).…”
Section: Discussionsupporting
confidence: 91%
“…The data from SPC-TNF-a mice in this study are in line with a study showing that mice lacking JNK1 are protected against TGF-b-induced pulmonary fibrosis and fibrotic gene expression (31,32). This is also supported by another study showing that JNK knockout mice were found to have an increased pulmonary elastin content compared with wild-type mice, and showed increased elastogenesis, but had impaired alveolar septation during lung development (33). In addition, the JNK inhibitor, SP600125, partly prevented bleomycin-induced hydroxyproline and a smooth muscle actin levels in the lung tissue of rats, and thalidomide, an immunomodulatory drug able to suppress the generation of TNF-a, prevented the induction of JNK phosphorylation and hydroxyproline and a smooth muscle actin levels even more (34).…”
Section: Discussionsupporting
confidence: 91%
“…10 The relatively small areas of lipidladen positive cells surrounding the vasculature within the lung tissue need further characterization. 54,55 We also detected extensive FABP4 labeling throughout both SU/hyp and control lung tissue not colocalized with the lipid-laden cells. FABP4 can also be produced by macrophages, which are readily abundant in both healthy lung tissue (alveolar spaces) and severe PAH-associated lung tissue (pulmonary lesions).…”
Section: Discussionmentioning
confidence: 83%
“…Elastic fibers originally provide recoil tension to restore the structure of vascular tissues or organs and are essential for their function 17 . However, once elastic fibers are produced in a disorderly manner, they diminish the proper function of organs, leading to-for instance-restrictive ventilatory dysfunction in PPFE patients 6,18 .…”
Section: Discussionmentioning
confidence: 99%
“…However, once elastic fibers are produced in a disorderly manner, they diminish the proper function of organs, leading to-for instance-restrictive ventilatory dysfunction in PPFE patients 6,18 . Regulators of elastogenesis include transforming growth factor-β, fibroblast growth factor-2, epidermal growth factor, and insulin-like growth factor-1 17 . It is unknown whether these mediators contribute to the formation of subpleural fibroelastosis or medial elastosis in PPFE.…”
Section: Discussionmentioning
confidence: 99%